Percepção sobre prevenção e controle da Covid-19 na população geral e de gestantes do município de Aroeiras, PB, Brasil - Barros, Elba Raissa Serafim Vasconcelos (2022)
The pandemic caused by the new coronavirus 2019 (COVID-19) has been having an unprecedented impact on the routine of individuals. New arrangements in the form of leisure, work, study, and health care have had to be structured, without ignoring precautionary measures against the virus. However, the information about the preventive actions and control of COVID-19 at the beginning of the pandemic caused a lot of discussion and confusion in the population by showing the ignorance of science about the disease and its forms of spread and transmission, as well as the difficulties faced by governments in health management during this critical moment. This research aimed to understand how the population of the territory of a basic health unit in the municipality of Aroeiras (PB) perceived the information on prevention and control of COVID-19, which prevention measures were adopted, as well as to describe the health conditions of pregnant women and newborns in the population studied. Thus, a cross- sectional, descriptive study with a quantitative approach was carried out, applying an online questionnaire through the Google Forms platform to users registered at the UBS of Aroeiras. Two products resulted from this dissertation: an original article resulting from the study with the general population and an original article carried out with pregnant women in the territory. Both papers come from a multicenter study conducted by researchers from FIOCRUZ. The results of the study with the general population showed the following findings: TV and/or internet newspapers were the most prevalent source of information. Only 7% said they trusted social networks and 6% trusted governments as a source of information. The most used prevention measure was the face mask. The perception of the seriousness of the disease was reported by 58% of the participants. As for the people who worked in some essential service, 93% were high school graduates or above. A total of 71% of the people who had someone in the household go out to work during the pandemic were of elementary school age or less. The use of alcohol gel was reported as the most important preventive measure in the opinion of 90% of high school and college graduates. The results of the study with pregnant women showed the following findings: The adoption to preventive measures was prevalent in the studied pregnant women. Only two of the fifteen participating pregnant women were affected by covid during pregnancy, both presented mild symptoms, however one presented premature labor and fetal death. Only 27% of the pregnant women received the COVID-19 vaccine during prenatal care. The importance of providing knowledge about the pandemic should not be underestimated since the mitigation of infection depends on excellent means and sources of information. Careful monitoring of pregnancies with SARS-CoV-2 is recommended, as medium- and long- term studies are still needed.